Coronavirus Disease 2019 Mitigation Strategies Were Associated With Decreases in Other Respiratory Virus Infections. (20th March 2021) - Sinha, Pranay; Reifler, Katherine; Rossi, Michael; Sagar, Manish
Abstract: Detection of diverse respiratory viruses in Boston was approximately 80% lower after practices were instituted to limit coronavirus disease 2019 (COVID-19) spread compared with the same time period during the previous 5 years. Continuing the strategies that lower COVID-19 dissemination may be useful in decreasing the incidence of other viral respiratory infections. Abstract : Incidence of diverse respiratory viruses decreased approximately 80% after mitigation practices were implemented to decrease SARS-CoV-2 transmission in Boston. These practices may prove helpful in limiting seasonal viral infections, particularly for vulnerable populations, even after the COVID-19 pandemic subsides